Nutrient turnover by large sulfur bacteria on the Namibian mud belt during the low productivity season - Chuang, Pei-Chuan; Anderson, Chloe H.; Kossack, Michael; Fabian, Jenny; Su, Chih-Chieh; Vosteen, Paul; Zabel, Matthias; Scholz, Florian; Schulz-Vogt, Heide N.; Sommer, Stefan; Dale, Andrew W. (Frontiers in Marine Science, 2022)
Surface sediments of the coastal mud belt in the Benguela Upwelling System (BUS) off Namibia host extensive communities of chemotrophic large sulfur bacteria (LSB) of the family Beggiatoaceae such as Thiomargarita spp. and Ca. Maribeggiatoa spp. In order to understand the role of these bacteria in N and P cycling, biogeochemical data from three sites in the mud belt were simulated with a biogeochemical model including LSB catabolic pathways. Organic carbon remineralization was dominated by reduction of sulfate to hydrogen sulfide (5.0 - 7.7 mmol C m-2 d-1). At the two stations where LSB were observed, produced hydrogen sulfide was almost completely oxidized by LSB using nitrate as the electron acceptor. Modeled rates of nitrate reduction to N2 by LSB were over two times higher than nitrate reduction to ammonium. This points towards a potential negative feedback by LSB on primary production. Furthermore, loss of fixed N strongly enriched the benthic fluxes in P relative to N. Although the model included intracellular polyphosphate accumulation by LSB and subsequent breakdown to phosphate, a clear link between polyphosphate dynamics and hydroxyapatite precipitation and burial could not be clearly substantiated. This is partly due to simplifying assumptions in the model and analytical uncertainties in distinguishing between authigenic hydroxyapatite and allochthonous hydroxyapatite (e.g. fish bones), both of which are major components of particulate P in the BUS. Our modeling suggests a significant control of LSB on benthic N and P fluxes to the water column. Given the extensive coverage of LSB on the shelf (> 30,000 km2), more accurate forecasts of nutrient cycling and primary production in the BUS necessitate a closer inspection of benthic P sources and sinks in the mud belt and a clearer understanding of the controls on the end product of nitrate reduction by LSB.